Levels of C-reactive protein compared with maternal leukocyte count in predicting histological chorioamnionitis in pregnant women with preterm prematur e rupture of membranes - Miranda Flores, Alan Francis (2017)
Objectives: To determine the usefulness of C-reactive protein level compared with maternal leukocyte count in the prediction of histological chorioamnionitis in pregnant women with preterm premature rupture of membranes. Design: Non-experimental, validation of diagnostic test study. Setting: Instituto Nacional Materno Perinatal, Lima, Peru. Participants: Pregnant women with preterm premature rupture of membranes (PTPROM), between January and June, 2013. Interventions: Pregnant women with gestational age ≥ 22 weeks and <37 weeks, with premature rupture of membranes, single fetus, medical history available and complete required information were included. The SPSS 19 program was used for statistical analysis. Main outcome measures: C-reactive protein level and leukocyte count diagnostic indices. Results: The incidence of histological chorioamnionitis was 76.3% (71/93). The mean age of pregnant women was 29.0+ -6.6 years. The rupture occurred more frequently in women 25-30 years (31.2%) at mean gestational age 29.3+ -3.4 weeks; it was more prevalent at 27-31 weeks of gestation (51.6%), in middle social risk nulliparae. The average latency period was 12.6+-10.9 days and birth occurred within 15 days of PTPROM (74%). The average CRP level was 29.6+-26.9 mg/L for histological chorioamnionitis with significant difference (p =0.00). Its sensitivity was 98.6%, specificity 45.5%, positive predictive value 85.4% and negative predictive value 90.9%. The ROC curve predicted histological chorioamnionitis with an area under the curve of 0.861 (95% CI: 0.77 to 0.95) (p=0.000); the cutoff point above which the risk of histological chorioamnionitis could be predicted was 12.45 mg/L. The white blood cell count was 15 519.5+-4 410.5 cells/mL, with no significant difference (p = 0.790). Its sensitivity was 52.1%, specificity 63.6%, positive predictive value 82.2% and negative predictive value 29.2%. The area under the ROC curve 0.714. (95% CI 0.587 to 0.84) showed statistical significance (p = 0.002), with the cutoff 13 490 cells/mL. Conclusions: The level of C-reactive protein was more reliable than the maternal leukocyte count in predicting histological chorioamnionitis in pregnant women with premature rupture of fetal membranes.